The use of fibrolytic enzymes on the performance, metabolism and feeding behavior of feedlot cattle fed diets which differ in terms of level and source of roughage - Monteiro, Ludmila de Souza (2018)
Given the barriers in the degradability of the fibrous fraction of feed, two experiments were conducted with the objective of evaluating the use of fibrolytic enzymes (EFE) with xylanase and cellulase activities in feedlot diets for beef cattle, originating this dissertation. In the first experiment, the objective of the study was to determine the effect of the fibrolytic enzyme in the diet of finishing feedlot Nellore bulls with diets containing two sources and two levels of roughage inclusion. Two hundred and sixty-four Nellore bulls (371 ± 18.7 kg) were distributed in 48 pens by initial BW in a randomized complete block design with a 2 × 2 × 2 factorial arrangement of treatments. The finishing period was 95 days and diets were composed, on DM basis, of EFE or not (0.75 ml/kg DM; ABVista, Marlborough, UK), 8.5 or 12.5% of sugarcane bagasse (SCB) or grass hay (GH), 59 or 55% of ground corn, 15% of corn gluten feed, 15% of soybean hulls, 1.5% of minerals and vittamins with monensin, and 1% of urea. Animal performance was not significantly affected by the addition of EFE (P>0.10). Dry matter intake was higher for treatments with 12.5% of roughage (P<0,01) and for treatments with GH (P=0,01), but G:F was higher for 8.5% of roughage (P<0,01) and tended to be higher for SCB (P=0,07). Observed net energy concentrations were higher for 8.5% of roughage inclusion (P<0,01) and for SCB (P=0,04). In the second experiment, the objective was to evaluate ruminal parameters, total tract digestibility, and feeding behavior of 8 Nellore steers (396 ± 1.4 kg) receiving the same diets that the performance trial. The steers were assigned to two independent 4 × 4 Latin Squares (LSQ) with a 2 × 2 factorial arrangement of treatments, in which each LSQ received one different source of roughage. For steers fed SCB, digestibility of nutrients were not affected by the level o roughage nor by the presence of EFE (P>0.10). For steers fed GH the digestibility of CP was higher for 8.5% than for 12.5% of dietary roughage (P=0.01). The supplementation of EFE tended to increase the digestibilities of DM (P=0.08) and of CP (P=0.06) of GH diets. For animals fed SCB the molar proportion of isovalerate (P<0.01) was lower with 12.5% of dietary roughage and there was a tendency of reduction on total VFA concentration (P=0.06) and on molar proportion of valerate (P=0.07) compared to 8.5% of SCB. The EFE supplementation tended to increase the molar proportion of isovalerate (P=0.09) for SCB diets. In GH treatments, the acetate:propionate ratio was lower with the inclusion of 8.5% of roughage (P=0.04). The EFE supplementation tended to decrease the molar proportion of propionate (P=0.06), and increased the acetate:propionate ratio (P=0.03) and the molar proportions of isobutyrate and isovalerate (P<0.01). To conclude, the EFE supplementation do not improve the performance of feedlot cattle fed diets containing SCB or GH, but result in some positive effects on digestibility and in some effects on ruminal parameters of animals fed GH. The inclusion of 12.5% of SCB or GH in diets of feedlot cattle containing ground flint corn, soybean hulls, and corn gluten feed increase DMI, but decrease G:F compared to the inclusion of 8.5% of these sources of roughage. On level of inclusion of 8.5 or 12.5% of DM, SCB reduces DMI, with no alteration on ADG, and consequently improves G:F of feedlot cattle containing ground flint corn, soybean hulls, and corn gluten feed.